2016
DOI: 10.1177/0193841x15625014
|View full text |Cite
|
Sign up to set email alerts
|

Assessing and Strengthening Evidence-Based Program Registries’ Usefulness for Social Service Program Replication and Adaptation

Abstract: Evidence-based program registries provide insufficient information to guide context-sensitive decision making about program replication and adaptation. Registries should supplement their evidence base with nonexperimental evaluations and revise their methodological screens and synthesis-writing protocols to prioritize reporting-by both evaluators and the registries themselves-of context-specific implementation factors that affect program outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 16 publications
1
41
0
Order By: Relevance
“…The descriptions of the included checklists suggested that five checklists were primarily intended to be used by practitioners [19, 42, 46, 48, 49], seven by decision makers (this could include practitioners, as well as program managers, policy makers, politicians, etc.) [8, 34, 36, 39, 44, 45, 47], four by primary researchers (to presumably improve conduct and/or reporting) [18, 24, 35, 41], and five of the checklists were aimed at assisting both decision makers and researchers in making assessments [9, 17, 37, 38, 40]. Four of the identified checklists were intended for systematic review authors [11, 20, 43, 50] (see more details regarding these checklists in Table 3).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The descriptions of the included checklists suggested that five checklists were primarily intended to be used by practitioners [19, 42, 46, 48, 49], seven by decision makers (this could include practitioners, as well as program managers, policy makers, politicians, etc.) [8, 34, 36, 39, 44, 45, 47], four by primary researchers (to presumably improve conduct and/or reporting) [18, 24, 35, 41], and five of the checklists were aimed at assisting both decision makers and researchers in making assessments [9, 17, 37, 38, 40]. Four of the identified checklists were intended for systematic review authors [11, 20, 43, 50] (see more details regarding these checklists in Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…The majority of the 25 checklists were developed for use in health research ( N = 23). However, two checklists were developed for assessing research on interventions within the social sciences [44, 50]. All of the included checklists were aimed at assessing effectiveness research (quantitative data).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations